Integration with Secondary Stakeholders and Its Relationship with Sustainable Supply Chain Practices in Colombian SMES - Quiroga-Calderón, Laura M.; Mejía-Salazar, Ismael S.; Moreno-Mantilla, Carlos E.; Loaiza-Ramírez, Juan P. (European Journal of Sustainable Development, 2018)
The study of the relationship between the integration of Small and Medium-sized Enterprises (SMEs) with external stakeholders (e.g., NGOs, academia, the regulator, or communities) and the implementation of green and social practices in SMEs’ supply chains has received little attention in the literature. Hence, this research studies whether Green Supply Chain Management (GSCM) practices and more disruptive innovations involving the redefinition of the supply chain’s strategy are influenced by firms’ integration with this type of stakeholders. A survey questionnaire with 50 items drawn from the literature was applied to a convenience sample of Colombian SMEs. Experts previously evaluated a pilot instrument in terms of face validity, and then a survey pretest was conducted. Lineal regression analysis was performed on single scores computed for latent variables validated through factor analysis. Results show that the integration between SMEs and the community influences both GSCM and disruptive practices, and there is also some evidence for the positive effect on the latter originated in the integration with NGOs. Finally, there is no evidence that integration with the regulator influences either the development of GSCM practices or disruptive innovations. Keywords: Sustainability, stakeholder integration, SMEs, environmental innovation, social sustainability, sustainable supply chain